BIODEGRADATION OF USED BABY DIAPERS USING CELLULOLITIC FUNGUS AND BACTERIA WITH SOLID FERMENTATION - Riryn Novianty; Andi Dahliaty; Nurul Iflah Nasution; Haryati Haryati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Nahdlatul Wathan Mataram, 2020)
Diapers are made by cotton and pulp containing cellulose that can be used as a substrate in the production of cellulose enzymes. The purpose of this research is to determine the ability of cellulolytic fungi Trichoderma asperellum LBKURCC1 and cellulolytic bacteria S-22 to degrade the used diapers containing urine by solid fermentation for 10, 20, and 30 days. The activity of crude extract of cellulose enzyme was observed with CMC 2% as substrate at pH 5,5 (Trichoderma asperellum LBKURCC1) and pH 7 (bacteria S-22 isolate), incubation temperature 40ºC during 30 minutes by using Nelson Somogyi’s method. The result showed that used diapers can be used as substrate for cellulose enzyme production by fungi Trichoderma asperellum LBKURCC1 with the highest activity of cruide extract cellulose enzyme obtained at 10th days solid fermentation of (1,891 ± 1,453) × 10-3 U / mL and by bacteria S-22 isolate at 20th days solid fermentation of (2,854 ± 0,019) × 10-3 U/mL. It can be concluded that bacteria S-22 isolate would degrade the used diapers better than fungi Trichoderma asperellum LBKURCC1. The result of this research compared to quality standards compost of SNI: 19-7030-2004 have not fulfilled, so it can not be used as compost.